Penile Length of Prepubertal Children in Surabaya - Susiana, Okta Margarita; Yuliawati, Tri Hartini; Purwanto, Bambang; Rezano, Andri; I’tishom, Reny (Althea Medical Journal, 2023)
Background: Early recognition of phallic size abnormalities is essential to identify underlying endocrine and genetic disorders. Parents are concerned regarding their son’s penis length, especially obese and short-stature boys. This study aimed to investigate the factors of penile length in prepubertal boys aged 9-11 in Surabaya.Methods: A cross-sectional analytic observational study was conducted between October and November 2021 during the community services program of the Andrology Study Program, Universitas Airlangga. One hundred forty-eight healthy boys aged 9-11 years were enrolled in this study. Penile parameters and anthropometric measures were recorded. Data were analyzed with Spearman Rho’s formula to correlate the variables studied.Results: The average penile lengths and penile circumference of the penis were 6.3±1.4 and 5.2±1.0 cm, respectively. This study found two boys with micropenis (1.35%) with normal and overweight body mass index (BMI). The penile length was positively correlated with height but not with BMI.Conclusion: Androgen and growth hormones significantly influence penile length. Children with abnormal BMI tend to have smaller penile sizes, associated with increasing androgen aromatization.